'Racy of the soil': Jason Sherlock, Gaelic games and the performance of Irishness as a racial identity. Issue 1 (1st December 2020) - Nakase, Justine
This article uses critical race and performance studies to analyse the Gaelic games as a racialized performance of Irish national identity. As a key project of the Irish Revival, the Gaelic games are not only one of the most popular sports in Ireland but have from their inception been used as a strategic performance of Irish identity. Historically, the Gaelic games allowed Irish athletes to embody an aspirational White masculinity; since then whiteness has become nearly synonymous with Irishness. Yet this conflation of race and nation has become increasingly problematic as the demographics of Ireland shift. While the Gaelic games are often lauded as a space for the integration of new migrant communities, the reception of minority ethnic Irish athletes reveals the limitations of this inclusion. Examining the career of Asian-Irish Gaelic footballer Jason Sherlock ‐ arguably the first 'superstar' of the Gaelic games ‐ this article argues that while Irish sport offers a performative space where exclusionary definitions of Irish identity can be challenged, these spaces are often conditional and constrained by larger attitudes around race and racism in the nation at large.